2009
DOI: 10.3109/00016480802654380
|View full text |Cite
|
Sign up to set email alerts
|

Uvulopalatopharyngoplasty in 158 OSAS patients failing non-surgical treatment

Abstract: In all, 76% of the patients underwent sleep recordings preoperatively and postoperatively. The oxygen desaturation index (ODI(4)) decreased from median 23 (range 6-100) to 8 (range 0-60), p<0.001. Criteria of success (>50% reduction and ODI<20), was 64%. The ESS value decreased from median 12 (range 0-21) to 6 (0-22), p<0.001. In all, 88% of the patients were satisfied. Four of 158 patients (2.5%) had serious postoperative complications. There was neither sequel of complications nor mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
6
16
1
Order By: Relevance
“…[10][11][12] All subjects, with 1 exception, were downstaged to mild residual OSA, allowing for the clinical cessation of nocturnal CPAP. The improvement in the RDI may lead to reduced long-term sequelae and may provide for increased adherence with CPAP for the subjects requiring intervention for residual disease.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] All subjects, with 1 exception, were downstaged to mild residual OSA, allowing for the clinical cessation of nocturnal CPAP. The improvement in the RDI may lead to reduced long-term sequelae and may provide for increased adherence with CPAP for the subjects requiring intervention for residual disease.…”
Section: Resultsmentioning
confidence: 99%
“…In our RCT, the median ESS score was halved from 12 to 6 in the intervention group, and this result is identical to those from a 1-year follow-up of 158 OSAS patients in a study from our group. 21 Furthermore, in our 15-year follow-up of another study of 50 OSAS patients, the median ESS score after UPPP was 6. 22 These findings are also similar to those in other studies investigating the effects of UPPP; for example, the one by Yaremchuk et al 23 and the multicenter study by Weaver et al 24 The fact that this RCT (level 1 evidence) found similar outcomes suggests that the results from previous case series are reasonably accurate, because this RCT validates the results of these previous case series studies.…”
Section: Discussionmentioning
confidence: 72%
“…The median ESS score had significantly decreased from 12 (range 8-21) to 6 (2-16) (P < 0.001) in the intervention group, a mean reduction of 5.7 (3.9). The corresponding change for the control group was nonsignificant, from a median of 13 (8-18) to 12 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), with a significant difference between the groups (P < 0.001) (Fig. 2).…”
Section: Changes In the Epworth Sleepiness Scalementioning
confidence: 92%
See 1 more Smart Citation
“…Uvulopalatopharyngoplasty (UPPP), one of the most common surgical procedures for the treatment of OSAS, was demonstrated to be effective and safe. [2] However, the postoperative period after UPPP is often challenging as children with OSA undergoing UPPP are at significant risk of respiratory and cardiovascular complications. [3] They also need to be adminstered effective and safe perioperative analgesia with effective prevention of emergence agitation (EA).…”
Section: Introductionmentioning
confidence: 99%